Validation of the shortest version of the eating attitude test (EAT-7) as a screening tool for disordered eating in patients with first-episode schizophrenia - Feten Fekih-Romdhane; Youssef Boukadida; Majda Cheour; Souheil Hallit (Journal of Eating Disorders)
Abstract Background Individuals diagnosed with schizophrenia have a two to five-fold higher risk of developing obesity and up to threefold higher risk of developing disordered eating behaviors relative to the general population. Over the past decades, the Eating Attitude Test (EAT) has been well-recognized and widely used in clinical practice. However, only little psychometric information is available on the EAT for researchers and clinicians who deal with patients with schizophrenia, and it is still unclear whether the scale could fulfill measurement needs and help clinical and research decision-making in the context of psychotic disorders. This study aimed to investigate the psychometric properties of the shortest version of the EAT (EAT-7) among newly-diagnosed patients with schizophrenia who had minimal exposure to antipsychotics at the start of the study. Methods This is an observational, cross-sectional survey that was carried out in the department of psychiatry at Razi Hospital, Manouba, Tunisia. The study took place between January and June 2024, and involved clinically-stabilized outpatients with schizophrenia who have had < 3 months of treatment with antipsychotics (N = 112; mean age of 24.44 ± 5.41 years). Results In terms of factor analysis, the EAT-7 presented a one-dimensional structure. All seven items strongly loaded on a single factor, with all indices of the CFA suggesting a good fit to the data. In addition, the EAT-7 yielded excellent reliability coefficients, with both a McDonald’s ω and a Cronbach’s α of 0.88. Measurement invariance of the EAT-7 across sex groups was tested using multi-group CFA, and established at the configural, scalar, and metric levels. No significant differences in EAT-7 scores between males and females were found. Finally, EAT-7 scores positively correlated with scores of depression and anxiety, supporting concurrent validity of the scale. Conclusion The shortness, items’ clarity and conciseness of the EAT-7 make it an efficient tool appropriate as a first-step screening tool to detect disordered eating in patients with schizophrenia at low cost and burden. We hope that this study will facilitate the widespread application of the EAT-7 in routine assessment and monitoring of disordered eating in patients with schizophrenia, in both clinical and research practices.